MELODI DAN LIRIK LAGU CAMPURSARI CIPTAAN MANTHOUS - Kusnadi - (FBS UNY, 2006)
Campursari songs are specific phenomena in music development andJavanese traditional music. Based on forms, campursari songs composed byManthous still refer to traditional music and songs, especially the conventionalones, lelagon dolanan, or mixture between them. The most dominant literarydecoration applied in his song lyrics are purwakanthi guru swara, parikan,wangsalan, wancahan, the change of vowels at the end of stanzas, traditionalexpressions, senggakan and bebasan paribasan. The most dominant themes arelove, marriage life, beauty of nature and social life. All are in accordance withthe target of audience, namely youths and adults.Keywords: melody, lyrics, campursari songs